Estrutura da macrofauna e produção secundária bentônica em habitats vegetados e não vegetados de estuários tropicais na Ecorregião Marinha Leste do Brasil - Bissoli, Lorena Bonno (2016)
Estuarine ecosystems, composed by various habitats, including mangrove forests and tidal flats, support high productivity and a diverse community of benthic organisms. These habitats are spatially heterogeneous resulting in variable density, biomass and secondary production of benthic organisms, but the scales of their variability are poorly known in tropical estuaries. To assess the spatial variability of benthic macrofaunal secondary production, biomass, density and composition on mangroves (vegetated) and adjacent tidal flats (unvegetated), a nested protocol was used allowing determining what spatial scales were significant to each assemblage descriptor. Three tropical estuaries located in the Eastern Marine Ecoregion of Brazil were sampled (larger spatial scale) on one mesohaline region in both habitats at the scales of sites, plots and replicates (local scales). Changes in benthic assemblage composition, biomass, density and secondary production occurred mainly between habitats, with some differences among estuaries. At Benevente estuary, unvegetated habitats had higher macrofaunal secondary production, biomass and density, due to the dominance of Kalliapseudidae (Tanaidacea). However, the other two estuaries exhibited opposite patterns of macrofaunal biomass and secondary production, with higher values within mangrove forests which is consistent with previous observations in vegetated habitats from other estuaries. Taxonomic composition (family level) of benthic assemblages was more similar between vegetated habitats among estuaries, and related to higher sedimentary detritus biomass and total sedimentary organic matter in these habitats. Oligochaeta and Capitellidae dominated vegetated habitats, whereas unvegetated habitats exhibited variable dominance between estuaries. Mollusca and Crustacea exhibited higher biomass and were responsible for most of the secondary production at the studied estuaries, except at unvegetated habitat in Benevente estuary, where Kalliapseudidae was the family with higher production.